2013
DOI: 10.1002/ijc.28149
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial modulation decreases the bortezomib-resistance in multiple myeloma cells

Abstract: Multiple myeloma (MM) is an incurable hematological malignancy that causes most patients to eventually relapse and die from their disease. The 20S proteasome inhibitor bortezomib has emerged as an effective drug for MM treatment; however, intrinsic and acquired resistance to bortezomib has already been observed in MM patients. We evaluated the involvement of mitochondria in resistance to bortezomib-induced cell death in two different MM cell lines (bortezomib-resistant KMS20 cells and bortezomib-sensitive KMS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 32 publications
4
66
0
Order By: Relevance
“…Interestingly, we found that upregulation of LIG3 is associated to bortezomib resistance and that LIG3 downregulation is highly toxic and partially restore drug sensitivity in bortezomib-resistant cells. These findings could be consistent with recent evidence which showed that bortezomib resistance in malignant plasmacells is associated to high dependency on increased mitochondrial activity and that mitochondrial activity modulation decreases bortezomib resistance [57][58][59].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that upregulation of LIG3 is associated to bortezomib resistance and that LIG3 downregulation is highly toxic and partially restore drug sensitivity in bortezomib-resistant cells. These findings could be consistent with recent evidence which showed that bortezomib resistance in malignant plasmacells is associated to high dependency on increased mitochondrial activity and that mitochondrial activity modulation decreases bortezomib resistance [57][58][59].…”
Section: Discussionsupporting
confidence: 93%
“…Through the continued effort of many researchers, CSCs features have been revealed, such as anti-cancer drug resistance, metastasis, proliferation, hypoxic tolerance, and the capacity for neovessel induction [2,3] . Mitochondria-targeted drugs may overcome potentially the drug-resistance mechanisms that have progressed toward conventional chemo-therapeutics in cancer [4][5][6][7] . Mitochondria produce ATP, but they also mediate cell death and produce reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…8 In that report, we showed that MM cell lines had different susceptibilities against bortezomib according to their mitochondrial function. Specifically, KMS20 cells were resistant to bortezomib-mediated cell death.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, we reported a role for mitochondria in resistance to bortezomib-induced cell death and found that human MM KMS20 cells were resistant to bortezomib due to potentiation of mitochondrial function. 8 In that report, changes in the expression levels of certain genes, such as cyclophilin D, the mitochondrial calcium uniporter, and superoxide dismutase 2, led to changes in both mitochondrial activity and bortezomib susceptibility or resistance; their combined effects contributed to differential sensitivity or resistance of MM cells to bortezomib. Specifically, we showed that changes in mitochondrial reactive oxygen species (ROS) levels via depletion of superoxide dismutase 2 and treatment with 2-methoxyestradiol (2ME), known as a SOD inhibitor, induced bortezomib-resistant MM cell death.…”
Section: Introductionmentioning
confidence: 94%